2013
DOI: 10.1111/jan.12319
|View full text |Cite
|
Sign up to set email alerts
|

‘It's like a bag of pick and mix – you don't know what you are going to get’: young people's experience of neurofibromatosis Type 1

Abstract: Aims To explore the day‐to‐day experience of young people living with neurofibromatosis type 1 in the UK, focusing on the role that appearance plays in this experience. Background neurofibromatosis type 1 is a genetic condition, which is highly variable and unpredictable. It can result in varying degrees of visible difference (disfigurement). Both the effect of NF1 on appearance and its uncertainty can prove particularly difficult for those affected. However, very little research to date has investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…This contrasts with findings from interviews with young people with NF1 (Barke et al 2013) in which the young people themselves specifically highlighted that it was the uncertain nature of the condition and potential appearance changes rather than the current noticeability of NF1 that caused them the greatest concern. Parents felt that NF1 that was more visible to others impacted to a greater degree on their and their child's lives.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This contrasts with findings from interviews with young people with NF1 (Barke et al 2013) in which the young people themselves specifically highlighted that it was the uncertain nature of the condition and potential appearance changes rather than the current noticeability of NF1 that caused them the greatest concern. Parents felt that NF1 that was more visible to others impacted to a greater degree on their and their child's lives.…”
Section: Discussioncontrasting
confidence: 51%
“…Both the current study and concurrent research exploring the experiences of young people themselves (Barke et al 2013) have explored this overlooked area. Findings highlight the value parents place on information about NF1, access to health professionals with experience and knowledge of the condition and greater awareness and understanding of it amongst the general public, and teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there are few qualitative studies that explore the impact of NF1 upon the life and health of adults. Previous studies have identified negative impacts on social networks, worries about the unpredictability of disease, and concerns related to the cosmetic appearance of NF1 (Ablon 1999;Barke et al 2014;Benjamin et al 1993;Hummelvoll and Antonsen 2013;Mauger et al 1999;Smith et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous qualitative studies have focused on the impact of NF1 in adulthood, for instance, addressing the effects of plexiform neurofibromas (Lai et al, 2017), health and well-being, quality of life, and transition to adult care (Barke et al, 2014;Crawford et al, 2015;Draucker et al, 2017;Van Lierde et al, 2013). The aim of the current study was to provide more information on the full spectrum of worries and care needs in medical, psychological, social, and economic domains of adults with NF1 and parents of patients with NF1.…”
mentioning
confidence: 99%